Effect of distance above-ground on fungal colonization of blackgum and red oak ties during air-seasoning. (2nd July 2020) - Rogers, Leon; Cappellazzi, Jed; Morrell, Jeffrey J.
ABSTRACT: The effects of distance above ground on fungal colonization during air-seasoning were evaluated over time on blackgum ( Nyssa spp.) and red oak ( Quercus spp. Section Lobatae ) ties 150, 200, and 300 mm from the ground by culturing increment cores removed from three locations on each of 200 ties over the seasoning period. Fungi were present in many ties at the start of seasoning. Fungal isolations steadily increased with time, but there were no significant differences in frequency for ties seasoned at different sill heights for either timber species. The results indicate that lowering the sill height had no noticeable effect on the rates of fungal colonization of the timber species tested.